1997
DOI: 10.1007/s002130050305
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and uptake of 99m Tcexametazime shown by single photon emission tomography after oral idazoxan in probable Alzheimer-type dementia

Abstract: Preliminary reports suggest improved executive function in patients with lobar dementia after treatment with single doses of the alpha 2 adrenoceptor antagonist, idazoxan. The potential for use in probable Alzheimer-type dementia prompted the present study. Fifteen patients with probable Alzheimer-type dementia were examined twice with neuropsychological measures and 14 also with single photon emission tomography (SPET) after a single double blind oral administration of 40 mg idazoxan or placebo in a balanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Moffoot et al 1994). The involvement of ␣2-adrenoceptors in the improvement of fluency and spatial working memory observed in AD (the present study) and Korsakoff's psychosis or in healthy volunteers is supported by a recent report describing the effect of idazoxan, an ␣2-antagonist, on cognition (Goodwin et al 1997). Goodwin et al (1997) found that idazoxan treatment disrupted spatial working memory and word fluency in AD patients, and that the reduction in blood flow in the lateral prefrontal area correlated with impaired fluency performance.…”
Section: Discussionsupporting
confidence: 78%
“…Moffoot et al 1994). The involvement of ␣2-adrenoceptors in the improvement of fluency and spatial working memory observed in AD (the present study) and Korsakoff's psychosis or in healthy volunteers is supported by a recent report describing the effect of idazoxan, an ␣2-antagonist, on cognition (Goodwin et al 1997). Goodwin et al (1997) found that idazoxan treatment disrupted spatial working memory and word fluency in AD patients, and that the reduction in blood flow in the lateral prefrontal area correlated with impaired fluency performance.…”
Section: Discussionsupporting
confidence: 78%
“…The one functional imaging study comparing activation during the two types of ¯uency performance in healthy controls, however, revealed a similar pattern of activation and deactivation in a network involving both left frontal cortex and superior temporal regions [11]. Also, a study by Goodwin, et al [12] using Letter Fluency as an activation during SPECT in a sample of AD patients, revealed a circumscribed association between performance and left frontal activity at baseline, but a spreading of this association to incorporate temporopartietal regions on the right side during administration of the adrenergic a-2 receptor antagonist idazoxan, which impaired performance. Letter ¯uency performance appears to be aected, then, by regional brain activity beyond what is suggested by lesion studies.…”
Section: Introductionmentioning
confidence: 93%
“…This may have some relevance to the detrimental effect of IDZ in fvFTD patients on this task, in that IDZ may somehow have an 'overdose' effect upon performance, and highlights further the neural specificity of the deficits in fvFTD. It is notable that IDZ has also recently been found to produce deficits in spatial working memory in patients with pDAT [71].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%